MENENTANG SEKULARISME: Upaya Membentuk Kesalehan Subjek Muslim di Banten - Mohamad Hudaeri (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Contemporary Islamic movements have undergone many changes of outlook, social and political orientations. The movement is not directed to establish an Islamic state or to support the use of military forces to achieve individual and communal programs in preparing